The Effect of Rabal Probiotic Supplementation at Different Doses on the Growth and Survival of Striped Catfish (Pangasianodon hypopthalmus) using a Recirculation System - Citra Taulani; Mulyadi Mulyadi; Iskandar Putra (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Striped catfish is a consumable fish with a good selling price and is a leading export commodity in Indonesia. Striped catfish (Pangasianodon hypopthalmus) often experience slow growth due to several factors that affect metabolic efficiency and nutrient intake. This study aims to determine the optimal dose of rabal probiotics to improve the growth and survival of catfish using a recirculation system. This study was conducted from April to June 2025 for 50 days at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The method used was an experiment with a completely randomized design (CRD), using four treatments (P1 = control, P2 = Rabal probiotic 30 ml/100g feed, P3 = Rabal probiotic 35 ml/100g feed, P4 = Rabal probiotic 40 ml/100g feed) and three replicates. The results showed that administering Rabal probiotics at different doses affected the growth and survival of P. hypophthalmus in including average weight and length growth, specific growth rate, feed efficiency, feed conversion ratio, and survival. The best treatment was found in treatment P4 (40 ml/100 g feed), which showed significant growth (P<0.05), namely absolute length of 3.72 cm, absolute weight of 6.74 g, specific growth rate of 2.08%, FCR value of 1.43, feed efficiency of 69.93%, and survival rate of 85%.